"L' Insonne Da Tutta L'Eternità": La Croce di San Damiano alla luce della tradizione siriaca - Szymczak, Tomasz (Miscellanea francescana, 2024)
The San Damiano Cross was produced in the environment linked to the Syriac tradition. It is expected that it should be possible to interpret it also thanks to the light coming from this tradition. From various details of the Cross, the image of Jesus' open eyes is chosen for this study, thanks to the brief comparison with the image of the Crucifixion in the Rabbula Codex. Two other details of the San Damiano Cross should be added to this theme - the colour of Jesus' hair and his clothing. Reading the texts of the Syriac tradition allows us to indicate new paths of interpretation. In the section dedicated to Jesus' hair, the Italian translation of the Syriac version of the Letter of Lentulus is proposed.